Causal Relationships Among Tourism, International Trade, Pollution, and Economic Growth: Evidence from Central Asian Countries - Azam, Muhammad; Ahmad, Bilal; Ozturk, Ilhan (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study investigates the cointegration and causality among environmental quality (CO2 emissions), international trade, economic growth, and tourism of five Central Asian Republic States (CARS-5), namely Azerbaijan, Tajikistan, Kazakhstan, the Kyrgyz Republic, and Uzbekistan, for 1992– 2018. To this end, we employed the Johansen cointegration approach, modified Wald tests, and the Toda & Yamamoto (1995) approach. The empirical results showed that the variables were cointegrated in the long run, and the Granger causality test results revealed the existence of causality in the series. Furthermore, the empirical results validated both the export-led and the tourism-led growth hypotheses for Tajikistan and Kazakhstan. These findings suggest that the CARS-5 should develop appropriate and prudent public policies to stimulate sustainable economic development.